Genetically stratified Parkinson’s disease with freezing of gait is related to specific pattern of cognitive impairment and non-motor dominant endophenotype - Pavelka, Lukas; Rawal, Rajesh; Sapienza, Stefano; Klucken, Jochen; Pauly, Claire; Satagopam, Venkata; Krüger, Rejko (Frontiers in Aging Neuroscience, 2024)
Background: Freezing of gait (FOG) is an important milestone in the individual disease trajectory of people with Parkinson's disease (PD). Based on the cognitive model of FOG aetiology, the mechanism behind FOG implies higher executive dysfunction in PD FOG+ . To test this model, we investigated the FOG-related phenotype and cognitive subdomains in idiopathic PD (iPD) patients without genetic variants linked to PD from the Luxembourg Parkinson's study.Methods: Cross-sectional analysis of iPD FOG+ (n=118) vs. iPD FOG-(n=378) was performed followed by logistic regression models. Consequently, regression models were fitted in a subset of iPD FOG+ (n=35) vs. iPD FOG-(n=126) with detailed neuropsychological battery to assess the association of FOG with cognitive subdomains. Both regression models were adjusted for sociodemographic confounders and disease severity.Results: iPD FOG+ presented with more motor complications (MDS-UPDRS IV) compared to iPD FOG-. Moreover, higher non-motor burden was observed in iPD FOG+ , i.e. higher frequency of hallucinations, higher MDS-UPDRS I score and more pronounced autonomic dysfunction (measured by SCOPA-AUT). Additionally, iPD FOG+ showed lower sleep quality along with lower quality of life (measured by PDSS and PDQ-39 respectively). The cognitive subdomain analysis in iPD FOG+ vs. iPD FOG-indicated lower scores in Benton's Judgment of Line Orientation test and CERAD word recognition reflecting higher impairment in visuospatial, executive function and memory encoding.We determined a significant association between FOG and a clinical endophenotype of PD with higher non-motor burden. While our results supported the cognitive model of FOG, our findings point to a more widespread cortical impairment across cognitive subdomains beyond the executive domain in PD FOG+ with additional higher impairment in visuospatial function and memory encoding.